A Survey on Effects of Working Remotely on Job Performance in Banking Sector in Sabah, Malaysia - Siti Sarah Omar; Claraynce Henry (Journal of Techno-Social, 2024)
The research examines remote work’s impact on job performance in Sandakan’s banking sector, involving 112 employees across four different branches. The objectives are to scrutinize the relationship between remote work factors and job performance, with a focus on identifying the most influential ones. The study utilizes surveys and stratified sampling to comprehend the influence of remote work on job performance. The data analysis encompasses descriptive statistics, Spearman correlation, and multiple regression. The findings reveal that both technostress (r = -0.380, p < 0.001) and work environment (r = -0.332, p < 0.001) negatively impact job performance, suggesting that technological challenges and the work environment have an adverse influence on performance. On the other hand, remote communication (r = 0.386, p < 0.001) shows a positive correlation with enhanced performance. However, the study does not find a significant correlation between work-life balance and job performance (r = -0.049, p > 0.605). Multiple regression analysis confirms the significance of technostress and remote communication, with corresponding ? values of -0.199 (p = 0.043) and 0.581 (p < 0.001). The predictive models moderately accurately forecast outcomes, with R-squared values of 0.419 and 0.479 for remote communication and technostress. The findings underscore the importance of addressing technostress and enhancing remote communication for improving job performance. The study provides actionable insights for refining remote work setups, thereby benefiting employee outcomes.